#TITLE_ALTERNATIVE# - CHANDRA SUGIANTO (NIM : 12214080), WILLY
In order to meet the government's target in the National Energy Policy (Kebijakan Energi Nasional) on geothermal utilization for power plants, then it is currently conducting exploration and exploitation activities in several locations with considerable geothermal potential. Since geothermal development projects require very high cost and have high risk with low electricity selling price, a comprehensive feasibility study is needed to develop the project. In this study, it is conducted a technical and economical feasibility study of a power plant project from geothermal field X. The field is located in the eastern part of Indonesia with the proposed geothermal working area (WKP) at 10 coordinate points with a total area of Ã‚Â± 70,800 Ha. The field generally has 2 main reservoir blocks that have relatively no different characteristics. This study discusses the determination of reserves of geothermal fluid contained in the geothermal field X that can be use to generate into electrical energy, by firstly interpreting the data through the field study based on geological and geochemical survey results, also reservoir identification based on geophysical survey results. The determination of these reserves uses Monte Carlo Simulation with volumetric equations, so it is results in the probabilistic reserves distribution as follows; 10% probability (pessimistic) of 43 MW, 50% probability (moderate) of 75 MW, and 90% probability (optimistic) of 118 MW. This study also discusses the feasibility of project implementation economically, so it is necessary to establish economic model based on development scenarios which are also designed in this study for each probability reserves. The feasibility is reviewed through economical indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and Pay Out Time (POT). Under this study, by using the maximum electricity selling price in the local area based on the regulation, that is 8.44 UScents / kwh, the results of IRR value for all three cases (pessimistic, moderate, and optimistic) are quite good, with all positive NPV(@10%) values. Then all of PI value are greater than 1 and the POT is relatively good. Due to the condition of the prospective reserves and the results of economical indicator calculation, then all technical studies and economical analysis for each probability reserves in this study indicate that the power plant project in the geothermal field X is feasible to be developed further.